One-Stage Approach to Rehabilitate a Hopeless Tooth in the Maxilla by Means of Immediate Dentoalveolar Restoration: Surgical and Prosthetic Considerations - Gabriel Mulinari-Santos; Fabio Luiz Ferreira Scannavino; Erica Dorigatti de Avila; Luiz Antonio Borelli Barros-Filho; Leticia Helena Theodoro; Luiz Antonio Borelli Barros; Rafael Scaf de Molon (Hindawi Limited, 2024)
Contemporary dentistry has increased the demand for predictable functional and esthetic results in a short period of time without compromising the long-term success of rehabilitation. Recent advances in surgical techniques have provided alternatives that allow the prosthetic rehabilitation of complex implant-supported cases through minimally invasive techniques. In this context, immediate dentoalveolar restoration (IDR) was described aiming at restoring function and esthetics through the reconstruction of lost periodontal tissues followed by immediate implant placement in order to minimize treatment time and surgical morbidity in a one-stage approach. Therefore, the aim of this clinical case is to describe the reconstruction and rehabilitation of a hopeless tooth in the maxillary region in a one-stage approach by means of IDR. The proposed steps to rehabilitate the case involved atraumatic dental extraction, immediate implant placement, and hard tissue augmentation by means of cortical-medullary bone graft harvested from the maxillary tuberosity. Afterwards, a provisional restoration was manufactured and installed to the implant allowing immediate prosthesis provisionalization and function in the same operatory time. Six months after the surgical procedure, the final prosthesis was manufactured and installed. The follow-up of nine years demonstrated the preservation of hard and soft tissue without tissue alteration and a successful esthetic outcome. The surgical protocol used allowed the ideal three-dimensional placement of the implant with the restoration of the bone buccal wall, favoring the esthetic and functional outcome of the case with harmony between white and pink esthetics. In conclusion, the employed treatment validated immediate implant-supported restoration of the missing tooth with high predictability. Furthermore, this protocol resulted in fewer surgical interventions, regeneration, and preservation of peri-implant tissues reaching the patient's expectations.